Partisipasi Masyarakat Dalam Pembangunan Padat Karya Tunai Desa (PKTD) Di Desa Cisande Kecamatan Cicantayan Kabupaten Sukabumi - Asep Sudrajat; HANIFAH MAULIDAH (STISIP Widyapuri Mandiri, 2024)
This study aims to identify the problems of community participation in the Village Cash Labor Intensive Program (PKTD), which includes decision-making, activity implementation, monitoring and evaluation, and utilization of development results. This research uses a qualitative approach with descriptive methods and Yadav's theory in Mardikanto and Soebianto (2017) as the basis for analysis, which emphasizes four dimensions of community participation. The research was conducted in Cisande Village, Sukabumi District, with seven informants selected through purposive sampling and snowball sampling. The results showed that community participation in PKTD in Cisande Village was not optimal, as seen from the lack of community involvement and willingness in the implementation of development, as well as the lack of routine and periodic maintenance by the village government and the community.